Notch signaling induces a transcriptionally permissive state at the Complement C3d Receptor 2 (CR2) promoter in a pre-B cell model. (December 2020) - Ng, Han Leng; Taylor, Rhonda L.; Cheng, Jessica; Abraham, Lawrence J.; Quail, Elizabeth; Cruickshank, Mark N.; Ulgiati, Daniela
Highlights: CR2 is uniquely expressed on mature B cells. Notch signals induce CR2 mRNA expression in human pre-B cell line model. Following Notch signaling, dynamic chromatin changes observed within CR2 promoter. Notch signals change CR2 promoter from closed to transcriptionally permissive. Abstract: During mammalian lymphoid development, Notch signaling is necessary at multiple stages of T lymphopoiesis, including lineage commitment, and later stages of T cell effector differentiation. In contrast, outside of a defined role in the development of splenic marginal zone B cells, there is conflicting evidence regarding whether Notch signaling plays functional roles in other B cell sub-populations. Complement receptor 2 (CR2) modulates BCR-signaling and is tightly regulated throughout differentiation. During B lymphopoiesis, CR2 is detected on immature and mature B cells with high surface expression on marginal zone B cells. Here, we have explored the possibility that Notch regulates human CR2 transcriptional activity using in vitro models including a co-culture system, co-transfection gene reporters and chromatin accessibility assays. We provide evidence that Notch signaling regulates CR2 promoter activity in a mature B cell line, as well as the induction of endogenous CR2 mRNA in a non-expressing pre-B cell line. The dynamics of endogenous gene activation suggests additional unidentified factors are required to mediate surface CR2 expression on immature and mature B lineage cells.